Prevalence, patterns, and determinants of breastfeeding cessation among mothers of children under 24 months in Uganda - Florence Nakaggwa; Derrick Kimuli; Norah Namuwenge; Rebecca N. Nsubuga; Hellen Nayebare; Louis Kaboine; Immaculate Baseka; Kenneth Kasule; Sheila Nyakwezi; Solome Sevume; Norbert Mubiru; Barbara Amuron; et al. (BMC, 2024)
Abstract Background Breastfeeding duration is a critical component of infant and child nutrition, providing immediate and long-term benefits to both children and their mothers. This study uses data from the lot quality assurance sampling (LQAS) survey to examine the prevalence, patterns, and determinants of breastfeeding cessation in Uganda. Methods This study was a secondary analysis of data collected by the cross-sectional LQAS surveys in 2021 and 2022 covering 77 districts in Uganda. The LQAS survey methodology employs a systematic sampling approach to assess whether predefined quality standards are met within specific subgroups of a population. The study employed spatial analysis, bivariate analysis and logistic regression, both with and without clustering, to explore associations between independent variables and breastfeeding cessation. Unadjusted and adjusted odds ratios with 95% confidence intervals were calculated. Statistical significance was set at 5%. Results Overall, the study analysed 26,377 records of mothers with children under 24 months old. The mothers' mean age was 27.9 years while that of their children was 11.0 months. While the general breastfeeding cessation rate was 17.7%, cessation was highest (49.7%) among mothers of children 18-23 months. Factors associated with increased odds of breastfeeding cessation included older child's age, older mother's age, using modern family planning, being pregnant and having an unknown pregnancy status. Lower odds of breastfeeding cessation were observed among mothers who; were married, lived in larger households, lived in rural residences, whose children received vitamin A supplementation and among all other regions compared to Kampala. Conclusion One in five mothers cessed breastfeeding before their child reached 2 years, with a significant increase in cessation odds among mothers of older children. These findings underscore the importance of interventions to promote breastfeeding continuation and adequate nutrition for non-breastfed infants, particularly in regions with high cessation rates.